Service Quality with Patient Experience During the Covid-19 Pandemic - Ameliyah, Ayu Rizky; Nursapriani, Nursapriani (Jurnal Ilmiah Kesehatan (JIKA), 2023)
Service quality can be viewed from the aspects of technical quality and functional quality. Technical quality relates to the customer's view of the service output and functional quality relates to the service delivered from the service provider to the customer. The aim of this research was to analyze the relationship between service quality and patient experience during the Covid-19 pandemic at RSUP Dr. Tadjuddin Chalid Makassar. This type of research was quantitative research using a cross-sectional research design. The research was conducted at the Inpatient Installation of RSUP Dr. Tadjuddin Chalid Makassar with a research sample of 100 subjects regarding patient experiences during the Covid-19 pandemic. The data analysis used were univariate and bivariate. The data analysis used is univariate, bivariate and multivariate analysis. Bivariate used chi-square test and multivariate used linear regression. The results of this study showed that there was a relationship between doctor communication with p-value=0,009<0,05, nurse communication with p-value=0,000<0,05, responsiveness with p-value=0,000<0,05, medicine communication with p-value=0,000<0,05, and food service with p-value=0,000<0,05 on patient experience. Most patients stated that doctor communication, nurse communication, drug communication, responsiveness and food service were related to the patient experience. The variable that has the strongest relationship to patient experience is drug communication with an Exp (B) value of 7,634, which means drug communication is 7,6 times related to patient experience.